ROLE AND PLACE OF TECHNOLOGIES WEBINAR IN COOPERATION OF THE EDUCATIONAL PROCESS OF THE BRANCHES OF THE TASHKENT MEDICAL ACADEMY - Okhunov, A.O.; Khudaibergenova , N.Sh.; Atakov , S.S.; Bobabekov , A.R.; Kasimov , U.K. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
This article outlines the theoretical and practical aspects of using webinar technologies as an innovative form of education in the context of the formation of the information society. Models for the implementation of webinars in educational practice are presented in order to increase the effectiveness of education of students in the healthcare system. The proposed recommendations can be used in organizing the educational process in the system of distance education, including in the system of advanced training and professional retraining. Conclusion: When using distance learning, it is recommended to use almost all elements of the pedagogical and technological line: motivational and installation, informational, explanatory. When compiling the calendar-thematic plan of webinars, it is recommended to provide for several models for their implementation: individualized, network and mixed. When implementing the task of ensuring the quality of the educational process, lectures, in on-line mode, are recommended to be organized strictly on problematic topics with the participation of leading teachers. An important feature of webinars is that they can be "embedded" in the calendar-thematic lesson plan both in the form of on-line communication between the teacher and the student at the webinar, and in the form of quality control over students’ independent work using the distance education system.